Submission to NSW Parliament Inquiry into teacher shortages in New South Wales - Wilson, Rachel; McGrath-Champ, Susan; Gavin, Mihajla; Stacey, Meghan; Fitzgerald, Scott (2022)
The Teachers’ Work in Schools research team makes this submission to assist the Education Committee of the NSW Upper House in its “examination of teacher shortages in the NSW school system, both the factors contributing to the shortages” including “the various contributions of long-term teacher shortages, loss of the casual teaching workforce, vaccination mandates, COVID-19 and other factors”, and “the best ways to address them”. Together, over nearly ten years, through a series of research projects, the above colleagues at the University of Sydney, University of New South Wales, University of Technology Sydney and Curtin University have examined the issues of work, workload and conditions of work of Australian school teachers and school leaders. The past ten years have seen considerable shifts reported in the amount and nature of work undertaken by teachers. Our programme of research has documented these experiences and challenges, reviewing it nationally and in detail across state contexts, particularly NSW and also WA.